Leading in a VUCA Environment: V Is for Volatility - Kail, Col Eric G. (Harvard Business Review, 2010)
This post is part of an HBR Spotlight examining leadership lessons fro m the military This is the first in a series on the four aspects of VU CA, a framework used by the U.S. military to describe the environment in terms of volatility, uncertainty, complexity, and ambiguity. Do cha llenges and opportunities that once took days or […]
Keywords: Leadership